2014
DOI: 10.1038/npp.2014.183
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin Attenuates Neural Reactivity to Masked Threat Cues from the Eyes

Abstract: The neuropeptide oxytocin has recently been shown to modulate covert attention shifts to emotional face cues and to improve discrimination of masked facial emotions. These results suggest that oxytocin modulates facial emotion processing at early perceptual stages prior to full evaluation of the emotional expression. Here, we used functional magnetic resonance imaging to examine whether oxytocin alters neural responses to backwardly masked angry and happy faces while controlling for attention to the eye vs the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 48 publications
2
41
2
1
Order By: Relevance
“…This finding concurs with a recent study's data showing that oxytocin attenuates amygdala responses to threat cues from the eye region at very early stages of emotion perception (Kanat et al, 2015). In addition, oxytocin reduced the reactivity of the pulvinar, anterior cingulate cortex, and parts of the ventral stream to salient changes within the eye region on the neutral face mask irrespective of emotional meaning.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This finding concurs with a recent study's data showing that oxytocin attenuates amygdala responses to threat cues from the eye region at very early stages of emotion perception (Kanat et al, 2015). In addition, oxytocin reduced the reactivity of the pulvinar, anterior cingulate cortex, and parts of the ventral stream to salient changes within the eye region on the neutral face mask irrespective of emotional meaning.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, we examined whether a single dose of intranasal oxytocin would modulate responses of the amygdala and associated brain structures to masked fearful eye whites by means of a double-blind, placebo-controlled pharmacological protocol. As previous studies reported dampening oxytocin effects on amygdala reactivity to facial threat in men (Domes et al, 2007a;Kanat et al, 2015;Kirsch et al, 2005;Petrovic et al, 2008), we expected decreased amygdala responses to fearful eye whites following oxytocin as compared with placebo administration.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although this is consistent with our study in humans, lateralization is not commonly observed in macaques, and this finding deserves further research. Such lateralization is often observed in fMRI-OT studies with humans (Domes et al, 2007;Kanat et al, 2015) but hard to interpret, especially because other studies have also found left lateralization (Kirsch et al, 2005). To increase the repeatability of our experiment and reduce brain damage caused by the needle, we always injected OT or PLA at the same location in the right hemisphere.…”
Section: Limitationsmentioning
confidence: 97%